The meaning of adolescent reproductive health promotion through traditional arts: a community perspective - Ni Putu Widarini; Fatwa Sari Tetradewi; Ova Emilia (BKM Public Health and Community Medicine, 2021)
Objective: Knowing the perspective of the community watching reproductive health promotion activities through traditional art performances. Adolescent reproductive health promotion activities are carried out through the use of local wisdom in Bali, namely through the performance of traditional arts. The information conveyed through this promotional media contains informative messages about adolescent reproductive health so that it is no longer taboo to talk about and is easily accepted by the community. Methods: Qualitative research using an exploratory approach. The research location is in Tegallalang Village, Gianyar Regency, Bali. The informants were the people who watched the performance activities as many as 9 people. Retrieval of data through focus group discussions. Thematic data analysis. Result: The community's perspective on the performance and the message conveyed in the performance. The benefits of staging traditional arts according to the community watching are that socialization through art is easier to accept, traditional art performances can preserve culture and art, can be useful for society, namely reminding adolescents not to have premarital sexual behavior. The message received by the community is that there are limitations in dating, how to choose friends, carry out parental advice, anticipation of teenagers not having premarital sex and the impact of premarital sex. Acceptance of message content by the community, namely that the language is easy to understand, easily accepted by the community and becomes an example so that it is not imitated. Conclusion: Good interpretation of reproductive health promotion activities through the performance of traditional arts is related to the benefits and messages received by the community. The implication of the research results in the form of traditional art media as a health promotion media has the potential to educate the public in a positive way.